to achieve a Competitive Advantage Employing Lean Manufacturing System Using the Technology (Cellular Manufacturing) (Applied study in the State Company for Textile and Leather Industries - Leather Factory - Factory (7)) - Ayad Jasim Zopoon; Salma Mansour Saad (Journal of Madenat Alelem University College, 2022)
The developments that occurred in the industrial environment and the introduction of modern technology and automation in production processes, resulted in major shifts in production methods, which affected the competitiveness of the Iraqi industrial economic units, as most of these units suffer from weak ability to compete with imported products that invaded. The Iraqi market after 2003, due to its reliance on traditional systems in calculating costs and its lack of application of modern systems techniques that would reduce product costs to improve its competitive position, and among those systems is the Lean Manufacturing System, and that the adoption of the economic unit of this system contributes to reducing costs for what it has Techniques to achieve this.The current research aims to show how employing the techniques of the Lean Manufacturing System through one of its techniques represented by (Cellular Manufacturing) contributes to achieving a competitive advantage. This technology has been applied to the research sample (Leather Factory / Laboratory No. (7)) of the General Company for Industries Textile and leather, and the research came to the conclusion that the application of Lean Manufacturing System techniques achieves the objectives of the economic unit in obtaining a competitive advantage, by eliminating the waste caused by excessive work completion time as well as the high costs resulting from the unjustified increase in the number of workers.